The plasma corticosteroids: their determination and normal variations - Lewis, Barry (Division of Physiological Sciences, 2020)
The current interest in the secretions of the adrenal cortex is shared by physiologist, physician and pharmacologists alike. such attention is not surprising in the case of a gland which is immediately essential to life, which can produce syndromes as varied as precocious puberty, virilisation; Addison's disease; Cushing's syndrome, and the newly described hyperaldosteronism syndrome of Conn (1955), a gland which has been implicated in the parthenogenesis of diabetes (Hoet and Lukens, 195; Jackson, 1955), hypertension (Sepeika, 1948, 1955), pre-eclampsia, and atherosclerosis, and which profoundly effects so many of the metabolic processes of the body. The need for accurate measurement of adrenocortical function has therefore been accentuated in recent years. The purpose of this study was to find out as direct a method as possible for determining the rate of secretion of this gland and to define with this method the norms and normal variations.